A bibliometric analysis on the removal/recovery of ammonia from wastewater through precipitation in struvite (Research, Society and Development, 2020)
This paper aims to present a survey of publications that refer to the study of ammonia removal / recovery from wastewater through struvite precipitation, in order to seek recent studies of this century, and present an updated portfolio for future research. For the research, the Web of Science database was used, where a qualitative analysis was performed regarding the selected articles. In addition to the qualitative analysis, a bibliometric analysis of quotation and quotation was performed using the CiteSpace software and a network of collaborations was verified. Among the 11 selected journals, the most prominent magazine in relation to the theme is ENVIRONMENTAL TECHNOLOGY. It is observed that China has excelled in this matter. The results demonstrate that the studies analyzed have been looking for low cost reagents and at the same time employing struvite precipitation in different types of wastewater that have high concentrations of ammonia.